Three-Agenda Dynamics in The Kuhap Controversy: Media, Public, and Policy Agenda in Indonesia’s Digital Sphere - Suni, Yovandri Hendrikus; Epifania, Dolvina; Fauzy, Annas; Fazlur, Ayatullah; Laak, Deby Riani Prisca (Journal of Cultural Analysis and Social Change, 2026)
This study aims to analyze the dynamics of the KUHAP revision issue through the interactions among the media agenda, public agenda, and policy agenda, to understand how media coverage, public perceptions, and government responses collectively influence the construction of policy discourse. Employing a qualitative method with a Qualitative Data Analytic Software (Q-DAS) approach, the study traces patterns of exposure, keyword associations, conversation intensity, and temporal shifts in issue focus. Data were collected from online news media and social media between November 1 and 26, 2025, and classified into three phases: pre-viral, viral, and post-viral. During the initial phase, 1,205 news articles and 1,784 conversations were recorded; these numbers increased to 1,957 news articles and 73,418 conversations at the peak of virality, and then declined to 1,583 news articles and 14,597 conversations in the post-viral phase. The analysis reveals that the media agenda contributed to the early escalation by highlighting criticisms from academics and civil society regarding the erosion of due process, the expansion of investigative authority, and the potential for criminalization. This intensity fueled the public agenda, reflected in a surge of negative sentiment, particularly after the government’s responses on 18–19 November failed to ease public concerns. Subsequently, public pressure influenced the policy agenda, marked by discourse on article evaluation, plans for public consultation, and adjustments to communication strategies. However, these remained reactive and did not fully address substantive objections. This study highlights the continuous interaction among the three agendas that shape the trajectory of the KUHAP revision controversy, demonstrating how digital information dynamics can significantly impact policy processes.